Two Worlds - Everett-Camplin, Helen (Cambridge University Press United Kingdom, 2010)
Through different voices, this book explores the 'Two Worlds' of immigrants to Britain: the home they left and the home they are now in. The characters outline their reasons for leaving their home country and their impressions of the United Kingdom.
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents
Keywords: Fiction; Human interest; Reading books; Language Learning; Intermediate level; English language